Coordination of Actors in The Application of Child-Friendly City in Sidoarjo District - Isnaini Rodiyah; Roro Tantiko Dariyatun Nur Sanggito (Universitas Muhammadiyah Sidoarjo, 2021)
This study aims to analyze and describe the Coordination of Actors in the Implementation of Child Friendly Cities in Sidoarjo Regency. This type of research is descriptive research with a qualitative approach, the research location is at the Office of Women's Empowerment, Child Protection and Family Planning. the research informant is the Head of the Fulfillment of Children's Rights. Types of primary and secondary data using data collection techniques through observation, interviews and documentation as well as literature study. The technical analysis of data uses an interactive model by Miles and Hubermen, namely by data reduction, data presentation, and drawing conclusions or verification. The results of the study indicate that the coordination of actors in implementing child-friendly programs is carried out through planning meetings, implementing activities in accordance with the roles and functions of each actor..